The application of enterotoxigenic Escherichia coli (ETEC) K99, F41 polyvalent vaccine in pregnant dairy cattle to control neonatal colibacillosis and mortality of calves - ., Supar; ., Kusmiyati; Poerwadikarta, B (Indonesian Animal Sciences Society, 1998)
Enterotoxigenic Escherichia coli (ETEC) strains possessing either K99, F41 or K99F41 are responsible for causing neonatal diarrhoea and mortality of calves and difficult to control using antimicrobial drugs. A whole cell ETEC vaccine containing fimbrial antigens of polyvalent strains based on field serotypes was produced . The efficacy of ETEC vaccine used to control neonatal colibacillosis of dairy calves was studied in experimental animals and field trials. Five pregnant dairy cow were used for experimental study. Three animals were injected subcutaneously with 5 ml vaccine at 6 weeks and again 2 weeks before expected date of calving, others were left unvaccinated as control. Two calves born from vaccinated cows were given colostrum and milk from their own mothers. A calf born from vaccinated cow was not given colostrum, but milk from other vaccinated cow at day 8 . Three day old calves receiving colostrum of vaccinated cows were challenged with 2 ml either ETEC K99 or F41 suspension containing 108 colony forming units per ml did not show clinical signs of diarrhoea and their body weight increased progressively. Whereas, a calf born from unvaccinated group was challenged with ETEC K99 developed clinical sign of diarrhoea at 15 hours later and died at 8 days post-inoculation . A calf born from unvaccinated cow was challenged with ETEC F41 developed watery diarrhoea, it did not die, but its body weight relatively did not increase. The use of two doses ofpolyvalent ETEC vaccine at late gestation gave protection to the suckling offspring against challenged . Under farm conditions, dams vaccination with 2 doses of polyvalent ETEC vaccine 6 week and 2 weeks before expected date of calving reduced the calf mortality from average of 13% per months to 0.7%. It was concluded that dams vaccination with polyvalent ETEC containing K99 and F41 fimbrial antigens gave protection to their suckling offsprings or through consuming their colostrum or milk against homologous ETEC infection. Â Keywords: Calf, colibacillosis, ETEC, dams vaccination